2010
DOI: 10.1177/0734904109354966
|View full text |Cite
|
Sign up to set email alerts
|

A Different Approach to Vent Flow Calculations in Fire Compartments using the Critical Flow Condition

Abstract: In enclosure fires, density-driven vent flow through an opening to the fire compartment is directly dependent on the state of the fire and the evacuation of smoke and hot gases. If a fire is strongly under-ventilated, there may be heavy production of flammable gases. If a sudden opening occurs, e.g., a window breaks or a fireman opens a door to the fire compartment, fresh air enters the compartment and mixes with hot gases, thus creating a flammable mixture that might ignite and create a backdraft. In this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Fleischmann et al [4] first observed a particular shape of the velocity profile. Guigay et al suggested a profile similar to potential flow in a 180 degree bend around a wall end [3], as shown in Fig 13. …”
Section: Quantitative Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Fleischmann et al [4] first observed a particular shape of the velocity profile. Guigay et al suggested a profile similar to potential flow in a 180 degree bend around a wall end [3], as shown in Fig 13. …”
Section: Quantitative Resultsmentioning
confidence: 97%
“…This gives, at stable flow, the expression for the average velocity of the hot layer derived by the authors in Ref. [3]:…”
Section: Quantitative Results -Visualization With Fast Tomographymentioning
confidence: 99%
See 2 more Smart Citations
“…The work presented in this article is part of a PhD thesis called "CFD and experimental investigation of under-ventilated compartment fires" [1]. Its objective was to obtain a better understanding of gravity currents [2][3][4][5] and the resulting mixing in a fire enclosure. When an under-ventilated fire dies due to lack of oxygen, the enclosed room can remain full of hot unburnt gases.…”
Section: Introductionmentioning
confidence: 99%